Determinação das melhores condições de hidrólise física com ultrassom de potência em resíduos de amendoim - Polachini, Tiago Carregari [UNESP] (2015)
Nowadays, many resources are invested on developing new technologies for agroindustrial by-products utilization and process aiming at the second generation ethanol production. The peanut processing is one of the biggest waste producers, approximating to the waste from sugar cane culture. An emerging technology involved on residues treatment is the power ultrasound (US), which is being tested in areas such as cellulosic materials pretreatment and combined method to increase the reaction velocity in fermentative processes. In this work, powder peanut shells was obtained with an average particle size of 963,2 μm and density ranging according to its partice size. Its chemical characterization presented a dry matter composed by 37,1% of cellulose, 33,4% of hemicellulose and 15% of lignin. Initially, the acid suspension, which will be used in the physical hydrolysis, had its physical properties determined to allow the ultrasonic parameters calculation. Among the properties, there are density, rheological parameters and specific heat, where no influence of pH was verified. These properties could be modeled simultaneously as function of solid concentration and absolute temperature, through empirical and/or proposed models with good accuracy. Acoustic fields were determined and modeled, indicating higher cavitation effect in less concentrated suspensions when submitted to higher applied power. Throughout a experimental design, in suspensions at low biomass concentration (at high treatment time and applied power) occured higher total sugar release. Besides the consequent reducing sugar release, the amorphous and crystalline regions of cellulose could be affected. This fact evidenced the using of high-intensity ultrasound in pretreatment and its possibility as combined method applied to...